2013
DOI: 10.1016/j.jmii.2012.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological features of Chryseobacterium indologenes infections: Analysis of 215 cases

Abstract: The present study showed a trend of increasing prevalence of C indologenes infection after introduction of colistin and tigecycline usage. The bacteremia group had higher mortality rate than the pneumonia group. Increasing resistance to piperacillin-tazobactam, ceftazidime, cefepime, and newer fluoroquinolone were noticed in our analysis. Trimethoprim-sulfamethoxazole was a potential antimicrobial agent in vitro for C indologenes. To avoid collateral damage, we emphasize the importance of antibiotic stewardshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
127
0
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(154 citation statements)
references
References 23 publications
4
127
0
12
Order By: Relevance
“…C. oranimense has been reported to be isolated from raw milk (30), yet this is the first report of C. oranimense in humans, i.e., from a CF patient. Chryseobacterium species are multidrug resistant, with most intrinsically resistant to penicillin, first-and second-generation cephalosporin, aztreonam (14,33), and colistin (16), and have been reported to be acquired nosocomially via medical devices and contaminated water supplies in hospitals (18). Using a polyphasic approach, some studies have reported the presence of unusual bacteria, such as Acinetobacter spp., Bordetella spp., Comamonas spp., Rhizobium spp., Herbaspirillum spp., Moraxella spp., I. limosus, and Chryseobacterium spp., in the sputum samples from CF patients (34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…C. oranimense has been reported to be isolated from raw milk (30), yet this is the first report of C. oranimense in humans, i.e., from a CF patient. Chryseobacterium species are multidrug resistant, with most intrinsically resistant to penicillin, first-and second-generation cephalosporin, aztreonam (14,33), and colistin (16), and have been reported to be acquired nosocomially via medical devices and contaminated water supplies in hospitals (18). Using a polyphasic approach, some studies have reported the presence of unusual bacteria, such as Acinetobacter spp., Bordetella spp., Comamonas spp., Rhizobium spp., Herbaspirillum spp., Moraxella spp., I. limosus, and Chryseobacterium spp., in the sputum samples from CF patients (34).…”
Section: Discussionmentioning
confidence: 99%
“…There are about 283 reported cases of infections associated with C. indologenes (15,16). In a report by Chen et al, 215 clinical isolates of multidrug-resistant C. indologenes were identified after the increasing clinical use of colistin and tigecycline (16), a risk for patients who have undergone extensive administration of antibiotics for a long period (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The isolated colonies produced a yellow pigment although this property is characteristic for different species of Chryseobacterium (Bernardet et al 2005). It is known that Chryseobacterium is most commonly found in environments including water sources (Chen et al 2012). More recently, a number of Chryseobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…által fertőzött CF-betegek nagyobb valószínűséggel fertőzöttek P. aeruginosával vagy a B. cepacia complex valamely tagjával is [13]. Karbapenemekkel és aminoglikozidokkal szemben természetes rezisztenciát mutatnak [13,14]. A CIP, LEV, SXT és FEP eseteink ≥90%-ában hatékonynak bizonyult.…”
Section: Fontosabb Ritkábban Előforduló Gram-negatív Pálcák Jellemzéseunclassified